Sustainability of Cultural Identity of Ex-Adherents Kawula Warga Naluri of 1966-1971 in Banjarnegara, Indonesia - Sulani, Puji; Wibowo, Priyanto; Muas, Tuty Nur Mutia Enoch (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
This article describes the interaction between the structure and agency of ex-adherent of Kawula Warga Naluri in Banjarnegara District to maintain cultural identity and fight against the stereotype of "belum beragama" (does not belong to any religion) after the September 30th Movement incident in 1965. This article is a study of social history carried out through stages according to the rules of the historical method. The historical sources used are oral, namely historical actors and witnesses combined with written sources. Data obtained were analysed and interpreted using the structuration theory adopted from Giddens. This article produces an explanation of the reciprocal relationship between the structure of religious rules and socio-political conditions with the choice of Buddha Dharma as the religion of ex-adherent of Kawula Warga Naluri. The choice of Buddha Dharma is a form of rejection of the stereotype of "belum beragama" adherence to religious rules and persistence of cultural identity. In adapting to the Buddha Dharma, the ex-adherent of Kawula Warga Naluri face suspicious attitudes from the local government. The ex-adherent of Kawula Warga Naluri responds to this attitude in an accommodative and moderate manner. This article concludes that there is an interaction between structure and the act of disbanding, application of religious obligations, and the defense of cultural identity through Buddha Dharma by ex-adherent of Kawula Warga Naluri.